Efficient and Low-Cost 3D Structured Light System Based on a Modified Number-Theoretic Approach. (13th December 2009) - Pribanić, Tomislav; Džapo, Hrvoje; Salvi, Joaquim
Abstract : 3D scanning based on structured light (SL) has been proven to be a powerful tool to measure the three-dimensional shape of surfaces, especially in biomechanics. We define a set of conditions that an optimal SL strategy should fulfill in the case of static scenes and then we present an efficient solution based on improving the number-theoretic approach (NTA). The proposal is compared to the well-known Gray code (GC) plus phase shift (PS) technique and the original NTA, all satisfying the same set of conditions but obtaining significant improvements with our implementation. The technique is validated in biomechanical applications such as the scanning of a footprint left on a "foam box" typically made for that purpose, where one of the ultimate goals could be the production of a shoe insole.